Idiom Analysis in the Indonesian Subtitles of Harry Potter and the Chamber of Secrets (2002) and Harry Potter and the Prisoner of Azkaban (2004) - Akhdanil Ghifari; Agus Salim Mansyur; Andang Saehu (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Idiomatic expressions represent one of the most complex challenges in audiovisual translation due to their culture-specific nature and resistance to literal rendering. Despite growing scholarly interest in subtitle translation, studies focusing on idiomatic expressions in fantasy film subtitles within the English–Indonesian language pair remain limited. This study analyzes the types of idiomatic expressions and the translation strategies employed in the Indonesian subtitles of Harry Potter and the Chamber of Secrets (2002) and Harry Potter and the Prisoner of Azkaban (2004). A descriptive qualitative method was employed, with twelve idiomatic expressions selected and analyzed using Baker's (2011) framework. The findings reveal that pure idioms constitute the largest category (50%), followed by figurative idioms (33.3%) and semi-idioms (16.7%). Translation by paraphrase is the dominant strategy (66.7%), followed by using an idiom of similar meaning but dissimilar form (25%), and translation by cultural substitution (8.3%). The dominance of paraphrase reflects the significant cultural and linguistic distance between British English and Indonesian, which frequently necessitates the dissolution of culturally specific imagery in favor of communicative clarity. This study concludes that non-literal and adaptive translation strategies are essential in conveying idiomatic meaning effectively for Indonesian audiences.